Telephone-based cognitive behavioural therapy for patients with postoperative bariatric surgery to manage COVID-19 pandemic-related mental health issues and distress (TELE-BARICARE): a protocol for a randomised controlled trial. Issue 9 (15th September 2022) - Sockalingam, Sanjeev; Leung, Samantha Eve; Agic, Branka; Ma, Clement; Hawa, Raed; Wnuk, Susan; Dash, Satya; Jackson, Timothy; Akbar, Nadine; Forhan, Mary; Cassin, Stephanie E
Abstract : Introduction: Bariatric surgery is currently the most effective treatment for obesity, and is performed yearly in over 8000 patients in Canada. Over 50% of those who live with obesity also have a history of mental health disorder. The COVID-19 pandemic has made it difficult for people living with obesity to manage their weight even after undergoing bariatric surgery, which combined with pandemic-related increases in mental health distress, has the potential to adversely impact obesity outcomes such as weight loss and quality of life. Reviews of virtual mental health interventions during COVID-19 have not identified any interventions that specifically address psychological distress or disordered eating in patients with obesity, including those who have had bariatric surgery. Methods and analysis: A randomised controlled trial will be conducted with 140 patients across four Ontario Bariatric Centres of Excellence to examine the efficacy of a telephone-based cognitive behavioural therapy intervention versus a control intervention (online COVID-19 self-help resources) in postoperative bariatric patients experiencing disordered eating and/or psychological distress. Patients will be randomised 1:1 to either group. Changes in the Binge Eating Scale and the Patient Health Questionnaire 9-Item Scale will be examined between groups across time (primary outcomes). Qualitative exit interviews will be conducted, and data will be used to inform future adaptations of the intervention to meet patients' diverse needs during and post-pandemic. Ethics and dissemination: This study has received ethics approvals from the following: Clinical Trials Ontario (3957) and the University Health Network Research Ethics Committee (22–5145), the Board of Record. All participants will provide written informed consent prior to enrolling in the study. Results will be made available to patients with bariatric surgery, the funders, the supporting organisations and other researchers via publication in peer-reviewed journals and conference presentations. Trial registration number: NCT05258578 .